2010
DOI: 10.1007/s00508-010-1302-8
|View full text |Cite
|
Sign up to set email alerts
|

Gender aspects in medical publication – the Wiener klinische Wochenschrift

Abstract: Between 2001 and 2007 the percentage of manuscripts submitted to Wiener klinische Wochenschrift by female authors constantly increased and is now around 30%, reaching almost 50% in some specialties such as pediatrics. Nevertheless, there remains a massive gender imbalance in Wiener klinische Wochenschrift: review papers or invited editorials are only rarely authored by female researchers, a very low percentage of peer reviewers is female - although the quality of their reviews is generally better - and only on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 13 publications
3
33
1
2
Order By: Relevance
“…In particular contributions as fi rst author, corresponding author or senior author indicate the persons primarily responsible for the implementation of the project and the heading of research groups. In this issue of Wiener klinische Wochenschrift Heckenberg and Druml report gender imbalance of authorship of contributions to a peer-reviewed general medical-scientifi c journal, the "Wiener klinische Wochenschrift" during the past decade, from 2001-2009 [6]. Th e number of female fi rst authors increased continuously by 50% reaching 32% of all manuscripts in 2007, but remained stable thereafter.…”
Section: Science and Gender: Vision And Missionmentioning
confidence: 93%
See 2 more Smart Citations
“…In particular contributions as fi rst author, corresponding author or senior author indicate the persons primarily responsible for the implementation of the project and the heading of research groups. In this issue of Wiener klinische Wochenschrift Heckenberg and Druml report gender imbalance of authorship of contributions to a peer-reviewed general medical-scientifi c journal, the "Wiener klinische Wochenschrift" during the past decade, from 2001-2009 [6]. Th e number of female fi rst authors increased continuously by 50% reaching 32% of all manuscripts in 2007, but remained stable thereafter.…”
Section: Science and Gender: Vision And Missionmentioning
confidence: 93%
“…In the article by Heckenberg and Druml, there was no diff erence in the acceptance rate between women and men but female authors had a somewhat higher rapid rejection rate [6]. In many cases the reason was a less appealing, poor presentation of the results.…”
Section: Science and Gender: Vision And Missionmentioning
confidence: 97%
See 1 more Smart Citation
“…Laut der viel zitierten Studie von Wenneras und Wold [64] muss eine Frau 2,5-mal so produktiv sein wie ein Mann, um als gleich kompetent wahrgenommen zu werden. Auch andere Studien [10,11,31,33,57] [9] keine Unterschiede. Palomba [48] jedoch fand heraus, dass bei Frauen mit höherem Rang der Produktivitätsanstieg geringer ausgefällt, was man durch zwei Effekte erklären kann: Entweder haben Frauen im Mittel weniger Mitarbeiter unter sich als Männer auf derselben Hierarchiestufe (auch hierfür gibt es Hinweise) oder sie haben mehr Bedenken, sich auch bei einem geringen inhaltlichen Beitrag als Mitautor nennen zu lassen.…”
Section: Studien Zu Frauen Auf Gate-keeper-positionenunclassified
“…59 They found no indications of gender bias, although they were quick to add that five of the nine editors were women during the period of their study. 61 They found that equal percentages of submitted manuscripts had reached publication but that more manuscripts submitted by female first authors were 'rapidly rejected' -a consequence, they say, of women scientists' poorer presentation and tendency to 'sell themselves short'. Affiliational bias is the subject of considerably less commentary.…”
Section: Atkinson Notes That Many Authors Will 'Peddle Their Work' Unmentioning
confidence: 99%